Stability Constants of Metal Complexes of Dithiocarbamates - Yamuna, K.; Ramana, V.V.; Emmanuel, K.A.; Saraswati, K. (Asian Journal of Chemistry, 2010)
The stability constant of Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes with dithiocarbamates are studied in 60% ethanol-water mixture at 28ºC using the pH titration technique. It is observed that the overall stability constants are in the order of Mn(II) < Fe(II) < Co(II) < Ni(II) < Cu(II) > Zn(II).